Efficacy of Short-Term Antiarrhythmic Drugs Use after Catheter Ablation of Atrial Fibrillation-A Systematic Review with Meta-Analyses and Trial Sequential Analyses of Randomized Controlled Trials. - Weijie Chen; Hang Liu; Zhiyu Ling; Yanping Xu; Jinqi Fan; Huaan Du; Peilin Xiao; Li Su; Zengzhang Liu; Xianbin Lan; Bernhard Zrenner; Yuehui Yin (PLoS ONE)
Background The efficacy of short-term antiarrhythmic drugs (AADs) use compared with no-AADs prescription after catheter ablation of atrial fibrillation (AF) in preventing atrial arrhythmia recurrence is uncertain. Methods We searched PubMed, Embase, and the Cochrane Library through December 2015 to identify randomized controlled trials (RCTs) which evaluated the efficacy of short-term AADs use compared with no-AADs prescription after AF ablation in preventing atrial arrhythmia recurrence. The primary outcome was labeled as early atrial arrhythmia recurrence within 3 months after ablation. Secondary outcome was defined as late recurrence after 3 months of ablation. Random-effects model or fixed-effects model was used to estimate relative risks (RRs) with 95% confidence intervals (CIs). Results Six RCTs with 2,667 patients were included into this meta-analysis. Compared with no-AADs administration after AF ablation, short-term AADs use was associated with significant reduction of early atrial arrhythmia recurrence (RR, 0.68; 95% CI, 0.52-0.87; p = 0.003). Trial sequential analysis (TSA) showed that the cumulative Z-curve crossed the trial sequential monitoring boundary for benefit, establishing sufficient and conclusive evidence. However, compared with no-AADs prescription, short-term AADs use after AF ablation didn't significantly reduce the risk of late atrial arrhythmia recurrence (RR, 0.92; 95% CI, 0.83-1.03; p = 0.15). TSA supported this result; meanwhile the estimated required information size (1,486 patients) was also met. Conclusion Short-term use of AADs after AF ablation can significantly decrease the risk of early atrial arrhythmia recurrence but not lead to corresponding reduction in risk of late atrial arrhythmia recurrence.